Water governance for traditional Syrian resources Between disability insurance and guaranteeing the future (Damascus University Journal for the economic and Political sciences, 2021)
Effective water governance has become an essential component for achieving sustainable development in Syria, as the Syrian water crisis is a governance crisis in the first place, and among the most important obstacles to water management is the lack of clarity and overlapping responsibilities and the multiplicity of bodies responsible for water, the inefficiency of water institutions and the lack of water resources, as for the aspect of governance obstacles Rationalization that facilitates efficient water management is insufficient public awareness, lack of legislation and laws, their application, centralization of decision, absence of transparency and accountability, lack of community and beneficiaries in water management, and the last factor, i.e. community involvement, remains They are in these factors and constraints of governance that greatly affect the efficiency of water management.Therefore, decision-making mechanisms should include the principles of good governance such as transparency, integration ... This concept is rooted in five pillars: efficiency, economic and environmental sustainability, responding to socio-economic development needs, accountability to stakeholders and the public, and commitment to ethical and moral values ​​and should It includes institutional reform - which works on laws, regulations, judicial rulings, regulatory measures, customs, capacity-building, effective coordination, accountability and transparency, monitoring and evaluation, legislative reform and law enforcement, as it has targeted. To study to develop a vision for the future of water resources in the studied based on capacity and deepen the knowledge of building and institution-building and propose policies, planning and development system of laws allocated in the field of water resources and deepening awareness of water systems and the Syrians.
Keywords: governance; water; sustainable development; integrated water resources management